2017
DOI: 10.15171/ehem.2017.15
|View full text |Cite
|
Sign up to set email alerts
|

Role of organic matter, clay, and iron contents in the sorption of oxytetracycline on river sediments

Abstract: Background: Oxytetracycline (OTC) is a widely-used antibiotic; metabolism studies indicate only partial assimilation of it inside the body. Traditional wastewater treatment plants cannot remove OTC, and this results in the release of considerable amounts of the drug into aquatic environments. There is much concern over the role of residual antibiotics in the development of new generations of bacteria with modified resistance to the antibiotics. The present work investigated the possibility of OTC sorption on r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Marine sediments or montmorillonite with a higher clay content were reported having a higher adsorption capacity for tetracyclines (Xu and Li 2010). Barbooti (2017) demonstrated that adsorption of OTC on sediment is controlled mainly by the iron contents. Figure 3 illustrates the effect of phosphate concentration on OTC adsorption on sediments.…”
Section: Adsorption Isotherms Of Single Otc and Single Phosphate On Mmentioning
confidence: 98%
“…Marine sediments or montmorillonite with a higher clay content were reported having a higher adsorption capacity for tetracyclines (Xu and Li 2010). Barbooti (2017) demonstrated that adsorption of OTC on sediment is controlled mainly by the iron contents. Figure 3 illustrates the effect of phosphate concentration on OTC adsorption on sediments.…”
Section: Adsorption Isotherms Of Single Otc and Single Phosphate On Mmentioning
confidence: 98%
“…9 Several reports have investigated the adsorption of OTC to various clays as well as iron oxides, providing insights into possible mechanisms that inuence the interactions between OTC and minerals. [10][11][12][13] Moreover, Wang et al reported that the presence of natural organic matter could promote the adsorption of OTC onto sediments by activating the adsorbents' sorption sites and decreasing the activation energy induced by organic matter. 4 That is, these components are likely to play critical roles in the mobility of various antibiotics.…”
Section: Introductionmentioning
confidence: 99%
“…The texture, clay, extractible iron and organic content of the sediments were measured. Pyrolysis-gas chromatography activity, mass spectrometry analysis showed that there are 3 types of organic substances: Crude hydrocarbons, artificial, and plant residues (33). Malakootian et al conducted a study to remove acid red 18 dye contained in wastewater, which are untreated in the aqueous environment, using hybrid micro-electrolysis process, including iron and Charcoal under the influence of ultrasonic waves (Fe/C/US) (34).…”
Section: Introductionmentioning
confidence: 99%